2015
DOI: 10.1016/j.mee.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-a-chip devices: How to close and plug the lab?

Abstract: a b s t r a c tLab-on-a-chip (LOC) devices are broadly used for research in the life sciences and diagnostics and represent a very fast moving field. LOC devices are designed, prototyped and assembled using numerous strategies and materials but some fundamental trends are that these devices typically need to be (1) sealed, (2) supplied with liquids, reagents and samples, and (3) often interconnected with electrical or microelectronic components. In general, closing and connecting to the outside world these min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
276
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(290 citation statements)
references
References 201 publications
2
276
0
5
Order By: Relevance
“…Mark et al (2010), Iliescu et al (2012), Nge et al (2013), Temiz et al (2015), Kim and Meng (2015) The platform presented here is our attempt at creating a platform that can be used as widely as possible, but it is not possible to offer all advantages of other platforms, without any of their drawbacks. One of the advantages of this platform, a very thin channel wall, also is one of its drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Mark et al (2010), Iliescu et al (2012), Nge et al (2013), Temiz et al (2015), Kim and Meng (2015) The platform presented here is our attempt at creating a platform that can be used as widely as possible, but it is not possible to offer all advantages of other platforms, without any of their drawbacks. One of the advantages of this platform, a very thin channel wall, also is one of its drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…PTM is also increasingly integrated with other 3D printing processes to reduce the challenges of multicomponent assembly and to interface microfluidic devices with external systems 29 . Although some PTM devices can interface directly, whether, by punching holes (in a manner, similar to standard soft lithography processes) 36 , molding open wells 33,47 , and adding connectors during the curing process 34,37,48 , other PTM devices can interface indirectly by attaching to 3D-printed components that do have the desired interfaces 39 .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite significant research activities in this highly multidisciplinary field over more than two decades, only few concepts have ultimately reached the level of commercialization. Studies addressing this issue [3,4] identified the lack of standardization and integration as the main barriers to acceptance by the end-user and thus to commercial breakthrough: After acquiring one of the few commercially available microfluidic products, the operator may face difficulties in connecting the microfluidic device to ancillary hardware, such as external supplies, valves, pumps and other microfluidic components [5]. In contrast to assessments in the early stages [6], which predicted silicon-based microsystem technology as the most promising approach for microfluidic applications, soft-matter-based and hybrid solutions have become more significant [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electroactive polymers (EAPs), which can be divided into electronic and ionic EAPs, are discussed in the subsequent sections (Sects. 5,6). Generally speaking, electronic EAPs respond to electrostatic charges.…”
Section: Introductionmentioning
confidence: 99%